Turkish Children in Germany Learning Grammatical Categories in Turkish as a Mother Tongue - Kyuchukov, Hristo; Giray, Bariş (East European Journal of Psycholinguistics, 2017)
The paper presents and discusses findings from a recent empirical study involving 40 Turkish children aged between 4 and 6 years attending two kindergartens in Berlin in the districts of Wedding and Neukölln. They were tested for their knowledge and comprehension of different grammatical categories in Turkish. Children from Wedding were found to be much better in their knowledge of the grammatical categories in their mother tongue. The differences are statistically significant F (1, 32) = 6. 6258, p = 0. 01488 (p< 0.05). The children from the kindergarten in Neukölln demonstrated lower results in Turkish grammar comprehension and thus their achieved literacy in L1. References Bagdoshvili, S. (2010) Turkish Migrants in Germany. Unpublished MA Thesis. Tbilisi: Institute of European Studies. Barac, R., Bialystok, E. (2012) Bilingual effects on cognitive and linguistic development: role of language, cultural background, and education. Child Development, 83(2), 413-422. Çakir, M. (2002) The use of Turkish as the mother tongue in multicultural settings in Germany. Anadolu University Journal of Social Sciences, 2(1), 39-58 Cummins, J. (2001). Bilingual children’s mother tongue: Why is it important for education? Rights and responsibilities of educators of bilingual-bicultural children. In: Making a Difference in the Lives of Bilingual-Bicultural Learners, (pp. 15-20). L.D. Soto, ed. New York: Peter Lang. Cummins, J. (2016) Intercultural education and academic achievement: a fraimwork for school based policies in multilingual schools. Intercultural Education, 26(6), 455-468. Haug, S. et al. (2009) Muslimisches Leben in Deutschland. Nurnberg. Horrocks, D. and Kolinsky, E. (1996) Turkish Culture in German Society Today. Oxford: Berghahn Books. Johnston, J. (2015) Factors that influence language development. In: Encyclopedia of Early childhood development [online], Tremblay, R. E., Boivin, M., Peters R. De V., (eds.). Retrieved from: http://www.child-encyclopedia.com/language-development-and-literacy/according-experts/factors-influence-language-development. Schmitz, Anke and Olfert Helena (2013): Minderheitssprachen im deutschen Schulwesen – Eine Analyse der Implementierung allochthoner und autochthoner Sprachen. Zeitschrift für Fremdsprachenforschung, 24(2), 203-227. Skutnabb-Kangas (2005) Skutnabb-Kangas, Tove (2005). Linguistic Genocide. In: Encyclopedia of Genocide and Crimes Against Humanity, 3 Volumes, (pp. 653-654). Shelton, D. (ed.). New York: Macmillan Reference, USA. Treffers-Daller J., Sumru Özsoy, A., Roeland van Houtet, R. (2007) (In)Complete acquisition of Turkish among Turkish German bilinguals in Germany and Turkey: An analysis of complex embeddings in narratives. The International Journal of Bilingual Education and Bilingualism, 10(3), 248-276. Yazıcı, Z. (1999). Almanya ve Turkiye’de Anaokuluna Devam Eden 60-76 Aylar Arasındaki Turk Cocuklarının Dil Geli’imi ile Okuma Olgunlugˇu Arasındakiıliskinin Incelenmesi [Investigation of connections between language development and reading readiness ofTurkish nursery school children aged 60-76 months in Germany and Turkey]. Ph.D. thesis, Gazi University. Yazıcı, Z., İlter, B., & Glover, P. (2010). How bilingual is bilingual? Mother-tongue proficiency and learning through a second language. International Journal of Early Years Education, 18(3), 259-268.